Manajemen Risiko Pada Investasi Bisnis Properti Syariah - Sugianto, Sugianto; El Hakim, Muhammad Luqman; Sati Hana'an, Dea Sarah (Jurnal Ilmiah Ekonomi Islam, 2024)
Risk management in sharia property business investment is a crucial element in ensuring the sustainability and success of long-term investments. The sharia property business, which includes unique aspects such as sharia provisions, market fluctuations and regulatory changes, faces risks that need to be carefully identified, evaluated and managed. The risk management process involves the steps of identifying risks, determining risk tolerance, and using mitigation strategies, including avoiding, reducing, sharing, or accepting risks. Alignment with sharia principles and a deep understanding of property law are key. Portfolio diversification, continuous monitoring, and collaboration with sharia experts are important factors in maintaining a balance between potential profits and risks. By implementing effective risk management, investors can maintain sharia integrity while protecting investment value and achieving financial goals in a sustainable manner.